Secondary Metabolite Identification and Antibacterial Activity of Ethanol Extract of Coconut Husk (Cocos nucifera L.) Against Escherichia coli ATCC 25922 - Bernadeta Videlsia Ikun; Syahrir Syahrir; Nimas Prita Rahajeningtyas Kusuma Wardani; Muhajirin Dean (Lembaga Pengembangan Kinerja Dosen, 2026)
Secondary metabolites are bioactive compounds commonly found in plants and have potential as natural antibacterial agents. Coconut coir (Cocos nucifera Linnaeus), an abundant agricultural by-product, is known to contain various secondary metabolites such as flavonoids, tannins, terpenoids, and phenolic compounds, which have been reported to possess antibacterial properties. Escherichia coli is a pathogenic bacterium that frequently causes human infections and has shown increasing resistance to several antibiotics, highlighting the need for alternative antibacterial sources. Inconsistencies in previous studies regarding the antibacterial activity of coconut coir against E. coli indicate the necessity for further investigation. This study aimed to identify the secondary metabolite content and evaluate the antibacterial activity of ethanol extract of coconut coir against Escherichia coli ATCC 25922. This study was an in vitro laboratory experimental study with a descriptive–experimental approach. Identification of secondary metabolites was conducted qualitatively using phytochemical screening of the ethanol extract of coconut coir. Antibacterial activity was assessed using the disc diffusion method with a post-test only control group design against Escherichia coli ATCC 25922. The phytochemical screening results demonstrated that the ethanol extract of coconut coir contained flavonoids, tannins, terpenoids, and polyphenols. However, the antibacterial activity test showed no inhibition zones at all tested concentrations of the ethanol extract against Escherichia coli ATCC 25922. These findings indicate that although the ethanol extract of coconut coir contains several secondary metabolites, it does not exhibit antibacterial activity against Escherichia coli ATCC 25922 when tested using the disc diffusion method.